Beyond the Bounds : Open Theism and the Undermining of Biblical Christianity - John Piper; Piper, John, 1946-; Taylor, Justin, 1976-; Helseth, Paul Kjoss, 1962- (Wheaton, Ill. : Crossway Books, 2003)
A collection of essays written by theologians analyzing the issue of open theism. Discusses the question of God's ability to repent and the influence of Greek philosophy on Christianity.
The rabbis and the claims of openness advocates / Russell Fuller -- Genetic defects or accidental similarities / Chad Owen Brand -- True freedom : the liberty that Scripture portrays as worth having / Mark R. Talbot -- Why open theism is flourishing now / William C. Davis -- Veiled glory : God's self-revelation in human likeness / A.B. Caneday -- Hellenistic or Hebrew? / Michael S. Horton -- The inerrancy of Scripture / Stephen J. Wellum -- The trustworthiness of God and the foundation of hope / Paul Kjoss Helseth -- The gospel of Christ / Bruce A. Ware -- When, why, and for what should we draw new boundaries? / Wayne Grudem -- Grounds for dismay / John Piper.
Includes bibliographical references (p, [385]-400) and indexes.
Keywords: Open Theism; God -- Biblical Teaching